The impact of the climate agenda on the fuel and energy complex development in Russia - A. O. Gosteva; A. A. Seregina (Вестник университета)
The article discusses the current climate issues and history of international regulatory framework development in the field of energy considering the climate agenda. Moreover, the paper studies implementation and use of international experience in the fuel and energy complex of the Russian Federation, as well as legislative framework in the field of climate and measures of the policy implementation at the state and corporate levels. In the new realities, a number of corporations of the Russian fuel and energy complex have already started to implement projects aimed at achieving carbon neutrality in order not only to meet the goals of the agenda but also to improve their image and increase the level of trust between partners. Examples of reorientation of major Russian energy companies to cleaner types of fuel extraction and production, and their strategic plans and current results in implementing it have been considered.